2002
DOI: 10.1093/oxfordjournals.jbchem.a003313
|View full text |Cite
|
Sign up to set email alerts
|

The Ribosome Modulation Factor (RMF) Binding Site on the 100S Ribosome of Escherichia coli

Abstract: During the stationary growth phase, Escherichia coli 70S ribosomes are converted to 100S ribosomes, and translational activity is lost. This conversion is caused by the binding of the ribosome modulation factor (RMF) to 70S ribosomes. In order to elucidate the mechanisms by which 100S ribosomes form and translational inactivation occurs, the shape of the 100S ribosome and the RMF ribosomal binding site were investigated by electron microscopy and protein-protein cross-linking, respectively. We show that (i) th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
94
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(100 citation statements)
references
References 0 publications
5
94
1
Order By: Relevance
“…In stationary-phase bacteria, ribosomes become dimerized, which could represent a way to store them. 83,91 Upon readdition of nutrients, the ribosomes are released from their dimerized state within two minutes. 91 Thus, decreased translation is associated with stationary phase in bacteria.…”
Section: Quiescence In E Colimentioning
confidence: 99%
“…In stationary-phase bacteria, ribosomes become dimerized, which could represent a way to store them. 83,91 Upon readdition of nutrients, the ribosomes are released from their dimerized state within two minutes. 91 Thus, decreased translation is associated with stationary phase in bacteria.…”
Section: Quiescence In E Colimentioning
confidence: 99%
“…RMF associates 70S ribosomes to convert them to a dimeric form, 100S ribosomes, which is a storage form of ribosome with no translation activity (Wada et al, 1990). RMF binds the peptidyl transferase center or the P site to inhibit reversibly the translation activity of ribosomes (Yoshida et al, 2002(Yoshida et al, , 2004. YfiA and YhbH associates 70S and 100S ribosomes, respectively (Maki et al, 2000).…”
Section: Proteomics Study Of the Ecoli Ribosomes Using Rfhr 2-d Gel mentioning
confidence: 99%
“…In a recent study, it was demonstrated that RMF covers the peptidyl transferase center and the entrance of the peptide exit tunnel (42). The dimerization reaction is reversible, as the 100S ribosomes dissociate back into 70S ribosomes within 2 min after cells are transferred into fresh medium (36,41) and as protein synthesis and cell proliferation resume within 6 min (38).…”
mentioning
confidence: 99%